Inversion for Constitutive Model Parameters of Bird in Case of Bird Striking - Peng Yu; Siliu Yu; Sheng He; Xinheng Huang; Weijing Yun (Shock and Vibration)
The strike between flying birds and airplanes results in the unacceptable losses of aircraft structures. The normal approach to evaluate the bird impact resistance is the combined full-scale experimental-numerical study. However, the simulation results from the current available bird constitutive models are usually not in good agreement with the experimental data. Establishing a reasonable bird constitutive model is difficult and significant to the simulation of the bird striking process. In this paper, based on the displacement measurements of an aluminum plate subjected to soft body impact, an inversion of the bird constitutive model is conducted by using backpropagation (BP) neural network. A comparative evaluation of this inversion model and other constitutive models is carried out, indicating that the proposed inversion model is more reasonable.